2019
DOI: 10.1155/2019/7835420
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis as Rare Presentation of Herpes Simplex Virus Encephalitis

Abstract: Herpes simplex virus 1 is a prevalent neurotropic pathogen that infects and establishes latency in peripheral sensory neurons. It can migrate into the central nervous system and cause encephalitis. The association between herpes simplex virus encephalitis and cerebral venous thrombosis is rare, with a very limited number of case reports described in the literature, despite the recognized thrombogenic effects of the virus. A 44-year-old man was brought to the emergency department with generalized tonic-clonic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…However, the associated morbidity and mortality have decreased substantially [ 29 ]. Various organisms, e.g., viruses [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], tubercular [ 50 , 51 ], bacteria [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], protozoa and other parasitic infections [ [60] , [61] , [62] , [63] ] have led to the development of CVT. Infection, when considered to be a direct cause of CVT, can spread from structures either adjacent to dura matter (e.g., paranasal sinuses, nose, mastoid and orbit) or from a distant locus.…”
Section: Resultsmentioning
confidence: 99%
“…However, the associated morbidity and mortality have decreased substantially [ 29 ]. Various organisms, e.g., viruses [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], tubercular [ 50 , 51 ], bacteria [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], protozoa and other parasitic infections [ [60] , [61] , [62] , [63] ] have led to the development of CVT. Infection, when considered to be a direct cause of CVT, can spread from structures either adjacent to dura matter (e.g., paranasal sinuses, nose, mastoid and orbit) or from a distant locus.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we observed 18 stroke patients with CVST; The average age of patients was 49 years, 78% were younger than 55 years old, and more than 60% were women. CVST was reported as a consequence of various viral infections such as the Varicella Zoster virus, [86][87][88][89] Influenza virus, [90] Herpes Simplex virus, [91] SARS, [92] and SARS-CoV-2. [11,93] Classically CVST is considered to occur in young adults, with the predilection of women.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy is with acyclovir and anticoagulation, and the clinical improvement seropositivity prevalence is more than 60%. 9 …”
Section: Managementmentioning
confidence: 99%